2017
DOI: 10.3747/co.24.3380
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and Breast Cancer Stage at Diagnosis: A Population-Based Study

Abstract: PurposeThe objective of the present study was to use a large, population-based cohort to examine the association between metformin and breast cancer stage at diagnosis while accounting for mammography differences. MethodsWe used data from Ontario administrative health databases to identify women 68 years of age or older with diabetes and invasive breast cancer diagnosed from 1 January 2007 to 31 December 2012. Adjusted logistic regression models were used to compare breast cancer stage at diagnosis (stages i a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
(36 reference statements)
1
15
1
Order By: Relevance
“…A phase II clinical trial (NCT01589367, phase II, Table 2), compared the efficacy of a combination of letrozole (2.5 mg/day) and metformin (1000 mg/day for week 1, 1500 mg/day for week 2, 2000 mg/day for week 3) vs. letrozole (2.5 mg/day) and placebo, in ER-positive breast cancer patients [161]. A phase II (NCT01310231, phase II, Table 2) trial showed no significant association between the use of metformin and the stage of breast cancer, characteristics of the tumor at diagnosis, and survival of patients [162,163].…”
Section: Clinical Data and Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A phase II clinical trial (NCT01589367, phase II, Table 2), compared the efficacy of a combination of letrozole (2.5 mg/day) and metformin (1000 mg/day for week 1, 1500 mg/day for week 2, 2000 mg/day for week 3) vs. letrozole (2.5 mg/day) and placebo, in ER-positive breast cancer patients [161]. A phase II (NCT01310231, phase II, Table 2) trial showed no significant association between the use of metformin and the stage of breast cancer, characteristics of the tumor at diagnosis, and survival of patients [162,163].…”
Section: Clinical Data and Trialsmentioning
confidence: 99%
“…In spite of all the studies and data that supports the use of metformin as an anti-cancer agent in breast cancer, certain studies have failed to show any significant association between the use of metformin and the stage of breast cancer, characteristics of the tumor at diagnosis, and survival of patients [162,163]. Patients receiving concurrent metformin and radiation experienced increased locoregional toxicity, higher frequency of treatment breaks, and desquamation/dermatitis despite the fact that several preclinical studies have demonstrated the metformin treatment-associated sensitization to radiation therapy [198][199][200].…”
Section: Mixed Messages and Challengesmentioning
confidence: 99%
“…Preliminary population-based studies have shown that metformin does not affect BC staging in older women with long-standing diabetes. 132 These findings contrast with both the short-term window of opportunity studies and with functional research highlighted earlier that show an effect of metformin on tumour growth characteristics.…”
Section: Metformin and Bcmentioning
confidence: 61%
“…148,149 Conversely, conflicting clinical findings with regard to the efficacy and anti-tumour role of metformin have been reported in the literature, thus strengthening the need for further research. 132,150…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several data obtained both in vitro and in vivo suggest antiproliferative effects on tumor cells, and several molecular mechanisms have been described to account for these observations. In this regard, a number of clinical observations over the last few years indicate that metformin (used in doses between 0.5 and 1.5 mg/daily for at least six months) seems to reduce the risk of cancer development in diabetic patients and improve response to certain therapies and survival time in patients with certain types of cancers, such as non-small cell lung cancer [ 172 , 173 , 174 , 175 ], gastric cancer [ 176 ], colorectal cancer [ 177 , 178 ], prostate cancer [ 178 , 179 ], breast cancer [ 180 , 181 ] and pancreatic cancer [ 182 , 183 ]. These data, though still awaiting further validation, provide the basis for the use of metformin as an adjuvant therapy against cancer development and progression [ 184 , 185 , 186 ].…”
Section: Metforminmentioning
confidence: 99%